Freezing, melting and structure of ice in a hydrophilic nanopore - Moore, Emily B. (2010)
The nucleation, growth, structure and melting of ice in 3 nm diameter hydrophilic nanopores are studied through molecular dynamics simulations with the mW water model. The melting temperature of water in the pore was Tporem = 223 K, 51 K lower than the melting point of bulk water in the model and in excellent agreement with experimental determinations for 3 nm silica pores. Liquid and ice coexist in equilibrium at the melting point and down to temperatures as low as 180 K. Liquid water is located at the interface of the pore wall, increasing from one monolayer at the freezing temperature, Tporef = 195 K, to two monolayers a few degrees below Tporem. Crystallization of ice in the pore occurs through homogeneous nucleation. At the freezing temperature, the critical nucleus contains ∼75 to 100 molecules, with a radius of gyration similar to the radius of the pore. The critical nuclei contain features of both cubic and hexagonal ice, although stacking of hexagonal and cubic layers is not defined until the nuclei reach ∼150 molecules. The structure of the confined ice is rich in stacking faults, in agreement with the interpretation of X-ray and neutron diffraction experiments. Though the presence of cubic layers is twice as prevalent as hexagonal ones, the crystals should not be considered defective Ic as sequences with more than three adjacent cubic (or hexagonal) layers are extremely rare in the confined ice.